VALIDITAS E-CARD EDUDAYA: MEDIA PEMBELAJARAN BERBASIS ETNOMATEMATIKA DAN TEKNOLOGI DIGITAL UNTUK SISWA SD - Prastitasari, Herti; Prihandoko, Yogi; Sari Putra, Eka Cahya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop the e-Card Edudaya learning media based on the culture of South Kalimantan to improve numeracy literacy in elementary school students, particularly in the topic of flat shapes. Identified issues at Pelambuan 2 State Elementary School, Banjarmasin, include low student performance in understanding basic mathematical concepts and the lack of interactive learning media relevant to students' everyday lives. This research uses the Research and Development approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. During the Analysis phase, the problems in the school were identified, along with a needs assessment for students. The Design phase focused on creating an application that integrates interactive technology with local culture, while the Development phase resulted in the creation of learning content using video, images, and text, incorporating elements of South Kalimantan culture. Validation results from media experts, elementary education experts, and mathematics experts showed average scores of 90%, 89%, and 90%, respectively, indicating the application’s effectiveness in enhancing students' understanding of mathematics and numeracy